Understanding regression analysis : an introductory guide - Schroeder, Larry D.; Sjoquist, David L.; Stephan, Paula E. (Los Angeles, CA : SAGE Publications, Inc, 2017)
Understanding Regression Analysis: An Introductory Guide presents the fundamentals of regression analysis, from its meaning to uses, in a concise, easy-to-read, and non-technical style. It illustrates how regression coefficients are estimated, interpreted, and used in a variety of settings within the social sciences, business, law, and public policy. Packed with applied examples and using few equations, the book walks readers through elementary material using a verbal, intuitive interpretation of regression coefficients, associated statistics, and hypothesis tests. The Second Edition features updated examples and new references to modern software output.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Regression analysis